10-year follow-up results of the initial application of 3D-printed percutaneous guides in drilled decompression of femoral head necrosis - Shengtao Li; Jie Wang; Qiang Zhang (BMC Musculoskeletal Disorders)
Abstract Objective To explore the feasibility and clinical significance of computer-aided design 3D-printed percutaneous guides in femoral head necrosis drilling and decompression surgery, and compare it with traditional surgery under fluoroscopy. The study also reports the results of follow-up after 10 years. Methods A retrospective study was conducted on patients with femoral head necrosis who had undergone drilling decompression surgery from November 2011 to November 2015. There were 15 patients in the guide group and 15 patients in the control group, and all of them were followed up for 5 to 10 years after the surgery. All patients were staged according to ARCO staging based on imaging manifestations. The guide group used 3D-printed percutaneous guides designed with computer-aided design and printed using 3D printing technology, while the control group used traditional fluoroscopy for guidance. The study compared operative time, number of fluoroscopies, and guide needle adjustments. Results The baseline data did not differ statistically significantly. The guide group had significantly shorter operative times, fewer fluoroscopies, and fewer guide needle adjustments compared to the control group. The average operative time in the guide group was 27.8 min, with 11.2 fluoroscopies and 1.2 guide needle adjustments, while the control group had an average operative time of 44.4 min, with 34.4 fluoroscopies and 3.4 needle adjustments. There was no significant difference in preoperative Harris scores between the two groups, but both groups showed significant improvement in postoperative Harris scores. After 10 years, the guide group had fewer cases of femoral head necrosis progressing to advanced ARCO stages III or IV, and fewer cases requiring total hip arthroplasty compared to the control group. Conclusion The use of computer-aided design 3D-printed percutaneous guides in femoral head necrosis drilling and decompression surgery is feasible and clinically significant. It reduces operative time, fluoroscopy, and guide needle adjustments, and is more effective in preventing the progression of femoral head necrosis to advanced stages compared to traditional surgery under fluoroscopy.